Healthcare Advocacy & Legislation in the Philippines: Social Movement/Civil Society Alternatives to Privatization & Commodification - San Juan, David Michael (Social Sciences and Development Review, 2025)
The Philippine Health Insurance Corporation’s (PhilHealth) financial situation is in dire straits, with an official claiming that its actuarial life would last until 2027 only. To achieve free universal healthcare, alternative financing options for the Philippines’ national health care system would have to be considered. This paper aims to analyze historical government health care reform policies vis-à-vis social movement/civil society alternatives – and the corresponding paradigm shifts that they present – which culminate in the recently filed House Bill 9515 (“An Act Providing for a Free, Comprehensive, and Progressive, National Public Health Care System”) authored by the Makabayan Coalition – a bloc of grassroots partylists with strong links with social movements. House Bill 9515’s provisions would bring the Philippine system closer to Cuba’s and the United Kingdom’s systems which both offer useful springboards in making public health care free for all. Thus, the bill can potentially help the Philippines transition from privatization & commodification which have characterized the prevailing framework in the country’s health care system for decades now.
Keywords: healthcare reform; healthcare advocacy; free healthcare; social movements; anti-neoliberalism